2001
DOI: 10.1016/s0735-1097(01)01480-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of atypical atrioventricular node re-entrant tachycardia from orthodromic reciprocating tachycardia using a septal accessory pathway by the response to ventricular pacing

Abstract: The S-A-VA interval and PPI-TCL are useful in distinguishing atypical AVNRT from ORT using a septal accessory pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
189
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 11 publications
6
189
1
1
Order By: Relevance
“…34 Michaud et al 35 have proposed 2 additional criteria for differential diagnosis. The ventriculoatrial (VA) interval and tachycardia cycle length (TCL) were measured during tachycardia, and entrainment of the tachycardia was accomplished with RV apical pacing.…”
Section: Tachycardia Entrainmentmentioning
confidence: 99%
“…34 Michaud et al 35 have proposed 2 additional criteria for differential diagnosis. The ventriculoatrial (VA) interval and tachycardia cycle length (TCL) were measured during tachycardia, and entrainment of the tachycardia was accomplished with RV apical pacing.…”
Section: Tachycardia Entrainmentmentioning
confidence: 99%
“…Other studies: Premature right ventricular complexes pacing 14) and entrainment pacing for differentiating AVNRT from ORT has been reported in previous studies. [15][16][17][18] Michaud, et al 15) reported that the postpacing interval after entrainment of AVNRT by RV pacing exceeded the tachycardia cycle length by > 115 ms. Their method is often used to identify the septal AP. However, for left side AP, there may be some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…5 A postpacing interval-tachycardia CL (PPI-TCL) > 115 ms is usually consistent with AVNRT, while a PPI-TCL difference < 115 ms is consistent with AVRT. 6 Nevertheless, a PPI-TCL > 110 ms can occur with AVRT circuited by a left-sided AP, because the right ventricular pacing site is far from such a circuit. During a long RP interval SVT, a corrected PPI-TCL > 110 ms should also prompt the consideration of orthodromic AVRT employing an AP with delayed retrograde conduction.…”
Section: Incessant Tachycardia-induced Cardiomyopathy In a Childmentioning
confidence: 99%